The contribution of reform coalitions to inclusion and equity: lessons from urban social movements. Issue 1 (2nd January 2023) - Mitlin, Diana
ABSTRACT: Coalitional politics is being used by multiple urban social movements – and agencies that support their work – to address the scale and nature of disadvantage in towns and cities of the Global South. To advance our understanding about how coalitions might form and function effectively, this paper introduces and analyses four diverse exemplars that illustrate the approaches used. We find that coalitions have the potential to improve the relational capital of disadvantaged residents, increasing the legitimacy of their claims, advancing their interests and leading to pro-poor reforms. Coalitions enhance existing political opportunities and potentially improve the political opportunity structure. However, context matters, particularly the nature and extent of local democracy, and coalitions must operate in a space that is circumscribed and contested.